2023
DOI: 10.3389/fspas.2023.1147571
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the effect of upward propagating migrating solar tides with the TIEGCM-ICON

Abstract: Introduction: The vertical coupling of the lower and upper atmosphere via atmospheric solar tides is very variable and affects the thermosphere and ionosphere system. In this study, we use Ionospheric Connection (ICON) explorer data from 220–270 Day Of Year (DOY), 2020 when large changes in the migrating semidiurnal tide (SW2) and the zonal and diurnal mean (ZM) zonal wind occur within 8 days.Method: We use the ICON Level4 product, the thermosphere-ionosphere-electrodynamics general circulation model (TIEGCM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Liu et al., 2018), whereas the TIEGCM cannot self‐consistently resolve atmospheric processes below its 97 km lower boundary (Qian et al., 2014). Including ICON HMEs into the TIEGCM partially accounts for lower atmospheric effects by including data‐informed diurnal and semidirunal tidal propagation up from the lower atmosphere (Maute et al., 2023), suggesting that global‐scale waves from the lower atmosphere may play a role in STW generation. The presence of STW signatures in models with the lower atmosphere but their absence in those without suggests that the lower atmosphere plays an important role in STW generation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al., 2018), whereas the TIEGCM cannot self‐consistently resolve atmospheric processes below its 97 km lower boundary (Qian et al., 2014). Including ICON HMEs into the TIEGCM partially accounts for lower atmospheric effects by including data‐informed diurnal and semidirunal tidal propagation up from the lower atmosphere (Maute et al., 2023), suggesting that global‐scale waves from the lower atmosphere may play a role in STW generation. The presence of STW signatures in models with the lower atmosphere but their absence in those without suggests that the lower atmosphere plays an important role in STW generation.…”
Section: Discussionmentioning
confidence: 99%
“…The TIEGCM describes thermospheric and ionospheric dynamics, energetics, and chemistry, coupled with ionospheric electrodynamics (Qian et al., 2014; Richmond, 1995). In this study, we used TIEGCM‐ICON, ICON's Level 4 data product (Maute, 2017; Maute et al., 2023; Maute & ICON Team, 2022), which includes two runs of the TIEGCM: a simulation which incorporates data‐driven 42‐day averages of diurnal and semidiurnal tidal forcing at the 97 km lower boundary via the Hough Mode Extension (HME) from MIGHTI horizontal winds and temperatures (Cullens et al., 2020; Forbes et al., 2017), and one without such a tidal specification. The background at the lower boundary is obtained from global averages of horizontal winds (Drob et al., 2008) and neutral temperatures and densities (Picone et al., 2002).…”
Section: Methods: Observations and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The remainder of this paper is focused on characterizing, diagnosing and comparing the DZM thermosphere circulations, O/N 2 ratios, and electron densities (Ne) as a function of height (100-400 km), latitude (90°S-90°N) and day of year (DOY, 1-365) due (a) solely to observation-based tides propagating up from below 100 km altitude, and (b) solely due to solar flux and magnetospheric (hereafter "SM") forcing. This is accomplished using the version of the Thermosphere Ionosphere Electrodynamics General Circulation Model (TIEGCM) developed for the Ionospheric CONnections (ICON) mission, TIEGCM-ICON (Maute, 2017; see also Maute et al, 2023), which is forced at its lower boundary by the observed tidal spectrum; and an additional simulation with this tidal forcing omitted, supplemented by a third simulation with variable SM forcing replaced by constant SM forcing. The details of how these model results are manipulated to achieve our end goals is described in the next Section.…”
Section: Introductionmentioning
confidence: 99%
“…The additional DE3 can also generate SPW4 in situ as well as a longitudinally symmetric quatradiurnal tide that is, Q0. Maute et al (2023) analyzed ICON neutral wind observations from the August-September 2020 period following a Hough Model Extension tidal analysis. They showed that SW2 was upwardly propagating from 110 to 250 km in the upper atmosphere, and that the latitudinal and temporal variations of DW1, TW3 and QW4 migrating tides were closely related to that of SW2.…”
mentioning
confidence: 99%